Pelatihan Pembinaan Komite Sekolah dalam Menciptakan Belajar yang Aman di Kabupaten Aceh Utara - Yulia, Yulia; Jamaluddin, Jamaluddin (LPPM Universitas Malikussaleh, 2025)
The training for school committee development is one of the key strategies in creating a safe and conducive learning environment. As strategic partners of school principals and teachers, school committees play a significant role in supporting policy implementation and supervising the educational process. This community service program aims to enhance the role of school committees and the impact of their training in fostering a safe learning atmosphere in North Aceh Regency. The method used involved training school committee members and teachers. The results of the activity show an increased understanding among school committee members and teachers regarding their roles, functions, and responsibilities, particularly in establishing mentoring systems, advocating for school policies, and participating in strengthening a child-friendly school culture. The training also encouraged the development of effective communication between schools and the community. In conclusion, the school committee development training contributes positively to strengthening community participation and improving a safe, inclusive, and participatory learning climate in schools across North Aceh.